In silico Identification of miRNAs and Their Targets in Cluster Bean for Their Role in Development and Physiological Responses - Chaudhary, Vrantika; Jangra, Sumit; Yadav, Neelam R. (Frontiers in Genetics, 2022)
Cluster bean popularly known as ‘guar’ is a drought-tolerant, annual legume that has recently emerged as an economically important crop, owing to its high protein and gum content. The guar gum has wide range of applications in food, pharma, and mining industries. India is the leading exporter of various cluster bean-based products all across the globe. Non-coding RNAs (miRNAs) are involved in regulating the expression of the target genes leading to variations in the associated pathways or final protein concentrations. The understanding of miRNAs and their associated targets in cluster bean is yet to be used to its full potential. In the present study, cluster bean EST (Expressed Sequence Tags) database was exploited to identify the miRNA and their predicted targets associated with metabolic and biological processes especially response to diverse biotic and abiotic stimuli using in silico approach. Computational analysis based on cluster bean ESTs led to the identification of 57 miRNAs along with their targets. To the best of our knowledge, this is the first report on identification of miRNAs and their targets using ESTs in cluster bean. The miRNA related to gum metabolism was also identified. Most abundant miRNA families predicted in our study were miR156, miR172, and miR2606. The length of most of the mature miRNAs was found to be 21nt long and the range of minimal folding energy (MFE) was 5.8 to 177.3 (-kcal/mol) with an average value of 25.4 (-kcal/mol). The identification of cluster bean miRNAs and their targets is predicted to hasten the miRNA discovery, resulting in better knowledge of the role of miRNAs in cluster bean development, physiology, and stress responses.